Local time distributions of repetition periods for rising tone lower band chorus waves in the magnetosphere. Issue 20 (25th October 2015) - Shue, Jih‐Hong; Hsieh, Yi‐Kai; Tam, Sunny W. Y.; Wang, Kaiti; Fu, Hui Shan; Bortnik, Jacob; Tao, Xin; Hsieh, Wen‐Chieh; Pi, Gilbert
Abstract: Whistler mode chorus waves generally occur outside the plasmapause in the magnetosphere. The most striking feature of the waves is their occurrence in discrete elements. One of the parameters that describe the discrete elements is the repetition period ( T rp ), the time between consecutive elements. The T rp has not been studied statistically before. We use high‐resolution waveform data to derive distributions of T rp for different local times. We find that the average T rp for the nightside (0.56 s) and dawnside (0.53 s) are smaller than those for the dayside (0.81 s) and duskside (0.97 s). Through a comparison with the background plasma and magnetic fields, we also find that the total magnetic field and temperature are the main controlling factors that affect the variability of T r p . These results are important for understanding the generation mechanism of chorus and choosing parameters in simulations that model the acceleration and loss of electrons by wave‐particle interactions. Key Points: First statistical study on repetition period of chorus First local time distributions of the repetition period Main controlling factors of repetition period identified as the total magnetic field and temperature